Nutrient Assessment and Potential Renal Load of Solutes in Infant Powder Formulas Available on the Honduran Market - Di Iorio, Adriana Beatriz; Mera Cruz, Erika Yomalli; González De León Gómez, Aquileo Daniel; Hernandez Santana, Adriana (Acta Scientific Publications OPC Private Limited, 2020)
Introduction: TInfant formulas (FIP) are food products that have been modified to partially or totally satisfy the physiological needs of the baby, manufactured under the rules of the Alimentarius Codex. Objective: To evaluate whether the FIP available in the Honduran market comply with the international regulations European Soci ety for Paediatric Gastroenterology Hepatology and Nutrition (ESPGAN) and the European Technical Regulation (RTS), regarding the potential renal load of solutes (CRPS) and the content of vitamins, minerals and proteins. Methods: The sample was 39 FIP, descriptive statistics was used, a review of the nutritional labeling was performed and the CRPS of each FIP was estimated. Statistical correlation was established between minerals, proteins and CRPS using the SPSS 25.0 program. Results: 55% of FIP come from Mexico, the estimated CRPS is correlated with their protein content; FIP CRPS for > 1 year was 237.28 mOsm/L and 130.36 mOsm/L on average. A higher caloric and micronutrient concentration was observed in FIP for premature in fants. In all FIP, the macronutrient content was in accordance with the recommendations of ESPGAN and RTS. . Conclusion: FIPs of 0 - 12 months do not comply with the CRPS recommendation for the age of 0 - 6 months. The fat-soluble vitamins were located in the minimum limits established by the RTS. 5% of the FIP evaluated contained trans fatty acids and for over a year were above the maximum limit established for vitamin B3.